PERANCANGAN DAN PENERAPAN ALGORITMA NAKULA SADEWA UNTUK MENGATASI DUPLIKASI PEMILIHAN DI TEMPAT PEMUNGUTAN SUARA - Prayogi, Yogi Priyo; Wintolo, Hero; Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
The security o f election's data in a manual election process is susceptible to some fraud activity, one of them is voter's identity theft activity which will be used to vote more than one time. The regulation which allow the voter to vote on another town has became a hole that can be used the perpetrator to vote using stolen identity as no one knows him and his true identity. This fraud activity will have direct impact to the result o f election. This fraud can be contained by using Nakula Sadewa Algorithm which will analyze and compare the voter's home voting place to the voting place that the voter's use to do the voting activity. The voter's can still vote on another town, but heavily encouraged to vote on his hometown.